Unchaining Weber's Iron Cage: A Look at What Managers Can Do - Dyck, Bruno (Christian scholar's review, 2008)
Ever since Max Weber first named the iron cage over a century ago, people have been interested in unchaining it. Christians may have a particular interest in Weber’s analysis because it points to the influence of religious values both in supporting initially, and then potentially liberating humankind from, the iron cage. Bruno Dyck, Mitchell J. Neubert, and Kenman Wong describe what the four functions of management—controlling, leading, planning, and organizing—might look if managers were liberated from the iron cage thinking. They draw on organizational learning theory to describe a process managers can follow to unchain the iron cage, and they discuss implications for management theory and practice. Mr. Dyck is Professor of Management at the University of Manitoba, Mr. Neubert is Professor of Business at Baylor University, and Mr. Wong is Professor of Business Ethics at Seattle Pacific University.